Motivación laboral y su relación con el desempeño del personal de la Municipalidad Distrital de San Juan Bautista 2021 - Ruiz Olórtegui, Gilberto (2023)
The general objective of the research was to determine the relationship between work motivation and staff performance in the District Municipality of San Juan Bautista 2021. Being a quantitative study, with a descriptive-correlational level and a non-experimental design, it has selected a sample of 78 workers. The data collection has been carried out through the survey technique, using the questionnaire as a data recording instrument, therefore, after processing the data in the Excel and SPSS v26 programs, the work concludes that, Work motivation is considerably positively related to staff performance, contrasted with a relationship at the 0.914 level and significant at 0.000. Likewise, there is an average positive relationship between work motivation and performance in the personnel function, which has been contrasted by a correlation at the 0.681 level. At the same time, motivation maintains a considerable positive relationship with the individual characteristics of the staff, which has been contrasted by a correlation at the 0.830 level. Finally, motivation presents a positive and considerable relationship with the supplementary aspects of the personnel, which has been contrasted by a correlation at the 0.837 level.